Innovative development as the component of new quality management concept - Zanozovska, Oksana (My University, 2013)
The problems of healthy nutrition become burning problems in the postindustrial economy. Thus, the forming of the new industry, which will be based on the innovative technologies and healthy food products is determined by the demand of people in healthy food as one of the key factors of the life quality. Проблема здорового харчування в постіндустріальному суспільстві загострюється. Тому необхідним є створення нової концепції управління якістю на основі інноваційного підходу.
Keywords: інновації (економіка); innovation (economics); кафедра міжнародної економіки